INFLUENCE OF CLIMATIC FACTOR ON SPECIFIC CONSUMPTION OF GRAPHITIZED ELECTRODES - O. M. Grudnitskiy; A. I. Rozhkov; A. V. Feklistov (Литьë и металлургия)
It is shown that influence of climatic factor on production processes is necessary to be taken into account at planning of enterprise work: to carry out correction of production schedules, and also to vary specific norms of raw and materials consumption.